Wuthuga (dugong) population status in Gathaagudu (Shark Bay) sea country - Holly Raudino; Amanda Hodgson; Chris Cleguer; Kym Reeve; Molly Moustaka; Osmar Luiz; Simone Strydom; Kathy Murray; Neilisha Oakley; Tariq McDonald; Abby Leyendekkers; Jay Hayes; et al. (Frontiers in Marine Science, 2026)
Introduction Monitoring trends in wildlife populations and their response to pressures is integral but challenging for conservation managers. Wuthuga (dugongs (Dugong dugon)) are increasingly vulnerable as extreme climatic events, such as marine heatwaves and flooding, intensify with a warming climate and increasingly impact the seagrass they are dependent upon. Methods This study estimated wuthuga abundance using two methodologies: conventional observer aerial surveys, as part of a time-series of surveys, alongside aerial imagery, in Gathaagudu (Shark Bay), Western Australia in 2023. We compare the contemporary abundance estimates with long term monitoring data (1989 – 2018) to identify temporal trends in abundance and distribution. Results Over time the observer-derived estimates of wuthuga in Gathaaguda has ranged from the highest estimate in 1999 of 13929 (± SE 1652) to the lowest in 2023 of 8688 (± SE 1119). The wuthuga population has remained stable over time, with no statistical difference discernable when density is modelled. Methods were compared for the area of highest wuthuga density in 2023 (survey block 4), the observer-derived wuthuga abundance estimate was 4551 (± SE 926) and the image-derived estimate 5748 (± SE 1765). The abundance estimates yielded from both methodologies were not statistically different. For both approaches, abundance estimates were modelled using standard approaches to account for perception and availability bias. Of all wuthuga sighted in Gathaagudu in 2023, ~9.6% were calves, which is within the range of calf proportions found in past surveys. Discussion Due to wuthuga reproductive biology, the proportion of calves observed during aerial surveys may be a useful secondary indicator of population condition and seagrass availability preceding the survey. The proportion of calves observed in 2023 is an encouraging indicator of population condition. The relative stability and size of the Gathaagudu wuthuga population highlights its global importance to the persistence of the species.